O processo de raciocínio da teoria das restrições alinhado à teoria da visão baseada em recursos na geração da vantagem competitiva - Vallim, Carlos Roberto (2018)
This thesis relates the theory of constraints (TOC) with the resource based view (RBV) and uses its implications as strategy to obtain results and competitive advantage in the process of company management. During the last 30 years, much progress has been made in researching resources and constraints of companies. However, there are still gaps to be explored, such as the alignment of TOC to VBR. This research seeks to minimize this gap. This thesis aims to use the TOC thinking process (TP) as a tool for the management of resources’ constraints, and once aligned with VBR, as a strategy to gain performance and competitive advantage. In order to reach this objective, the research is backed by TOC and VBR theories by exploring the main authors' perspectives and researches, allowing the identification of points of convergence between both theories. The methodology rests on a qualitative and quantitative approach and it is based on a multiple case study in 13 units of the Unimed Vitória Health Cooperative, where it was used data triangulation through direct non-participant observation of interviews with decision-makers and the application of questionnaires to measure the main weaknesses of resources or undesirable effects, making it possible to identify the root problem of the company and the obstacles to a better performance. The results show that by aligning the two theories it was possible to analyze the intensity of weakness of the company's internal resources, to find the main undesirable effects, and to apply the cause-effect logic of the TOC TP, identifying: what to change? for what to change? and how to change? An action plan that allowed to identify the few causes that explain the many symptoms has been drawn up, that is, the constraints of resources that if eliminated or treated will result in gains of results. The research allowed to integrate two fields of knowledge and develop a new strategy to solve problems of restrictions in resources. The alignment between VBR and TOC enhances the use of VBR as a resource management strategy to performance improvement, as it uses TOC TP in the management of resources’ constraints. Managers perceive that the integration between the two theories can improve the management of resources and it represents a better and more accurate strategy for the decision-making process and for obtaining better results in the company.